EVALUASI DALAM PENDIDIKAN ISLAM ANAK USIA DINI - Lydia Sartika; Yusniarti (Jurnal Al Athfaal, 2023)
The background to this problem is a lack of understanding of the meaning of evaluation in early childhood Islamic education, so the aim of this research was to find out the meaning of evaluation in early childhood Islamic education. Evaluation means measuring or assessing something to achieve good results. Meanwhile, early childhood Islamic education is an educational service that aims to develop the potential for moral values, instill moral beliefs and knowledge of worship in students. So it can be concluded that evaluation is closely related to early childhood Islamic education because it measures or assesses students' behavior regarding moral values, moral beliefs in the learning process. In this research, researchers use qualitative research, where research with a qualitative approach is an effort to find the truth in a field through discovering strengths or capacities in each concept. The result of this research is an increase in knowledge about the meaning of evaluation in early childhood Islamic education, so that teaching staff understand better how to implement good evaluation in school learning.